Penilaian Business Sustainability Menggunakan Model European Foundation for Quality Management pada Tenant Wirausaha Merdeka - Maulana, Danis; Beauty, Nur Lailany Fenny; Rachman, Farizi; Akseptori, Ristanti (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research aim: Analyzing the impact of the EFQM 2020 model on assessing business sustainability and business orientation categories of Wirausaha Merdeka tenants using Structural Equation Modeling and EFQM self-assessment. Method: The research uses quantitative data, the SEM (Structural Equation Modeling) method, and EFQM self-assessment. Research Finding: The results of the SEM analysis reveal that organizational culture and leadership, driving performance and transformation, and strategic and operational performance positively influence business sustainability. On the other hand, purpose, vision, and strategy, creating sustainable value, and stakeholder perceptions negatively influence business sustainability. Additionally, engaging stakeholders does not influence business sustainability. Meanwhile, based on the EFQM self-assessment results, it is found that 5 tenants are product-oriented, 16 tenants are process-oriented, and 2 tenants are system-oriented. Theoretical contribution/Originality: This research extends the application of EFQM to more specifically measure the sustainability level of vocational tenant startups, mainly focusing on the specific dimensions of business sustainability. Practitioner/Policy implication: This study adopts the EFQM Model to assess the sustainability of vocational tenant businesses. This study will thoroughly analyze the scores obtained for each EFQM criterion and identify the critical factors contributing to business sustainability. The results of this evaluation will serve as a basis for formulating more targeted recommendations for improvement and development. Research limitation: The EFQM self-assessment focused solely on obtaining the business orientation category through questionnaire responses, lacking in-depth evaluation through interviews.